Impact of Teaching Assistance for Vocational Schools - Dewi, Tantri Kusuma; Yoto, Yoto (Jurusan Pendidikan Kesejahteraan Keluarga, Fakultas Teknik, Universitas Negeri Semarang, 2023)
Freedom of learning is freedom of thought, starting from teacher respecting learning changes in educational institutions in elementary, secondary, and tertiary schools. Teaching assistance is one of the Merdeka Belajar Kampus Merdeka (MBKM) programs launched by the government through the Ministry of Education and Culture. The teaching assistance program can be taken by students who have taken at least 80 credits of courses and get approval from the academic supervisor and head of the study program. This study used the Triangulation interview method conducted at SMKN 2 Jombang. The results of this research are positive and good for SMKN 2 Jombang. This is because students participate in helping with school activities, can help teachers with additional tasks, and can exchange knowledge with teachers. This program not only has an impact on SMKN 2 Jombang, but this teaching assistance activity also has an impact on students. With this activity, students can find out about school conditions and student character and gain experience on how to become a teacher. This experience can be a provision for students to become teachers in the future.